2012
DOI: 10.14797/mdcj-8-4-37
|View full text |Cite
|
Sign up to set email alerts
|

Bypass Surgery for Lower Extremity Limb Salvage: Vein Bypass

Abstract: Bypass surgery for limb salvage in cases of chronic limb ischemia is a well-established treatment modality. Use of an autogenous vein provides the best conduit for infrainguinal arterial bypass procedures, particularly for bypass to the infrapopliteal arteries. In this article, we discuss infrainguinal vein bypass surgery including indications, perioperative care, and long-term follow up. We also discuss the outcomes of the procedure with regard to patient survival and limb salvage. The autogenous vein continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Failure in salvaging the critical limb can lead to limb loss and the high cost of patient care following amputation [ 11 , 12 ]. While surgical or endovascular revascularization is currently utilized for the treatment of CLI with an acceptable success rate [ 13 , 14 , 15 ], for those patients who are not candidates for surgical or endovascular intervention and those who failed the revascularization or bypass occlusion, the clinical outcomes remain dismal [ 13 , 14 ]. Accordingly, an alternative strategy for the treatment of CLI patients who are refractory to conventional therapy is urgently necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Failure in salvaging the critical limb can lead to limb loss and the high cost of patient care following amputation [ 11 , 12 ]. While surgical or endovascular revascularization is currently utilized for the treatment of CLI with an acceptable success rate [ 13 , 14 , 15 ], for those patients who are not candidates for surgical or endovascular intervention and those who failed the revascularization or bypass occlusion, the clinical outcomes remain dismal [ 13 , 14 ]. Accordingly, an alternative strategy for the treatment of CLI patients who are refractory to conventional therapy is urgently necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In a 1986 randomized comparison of autologous saphenous vein and expanded polytetrafluoroethylene (ePTFE) grafts in infrainguinal arterial reconstructions, Veith et al 1 found similar rates of primary graft patency up to 2 years, but superior patency in autologous vein grafts beyond that through 6-year follow-up. Although autologous vein is widely considered the standard for patency, limb salvage, and long-term survival, [2][3][4] it is not always available or appropriate for above-knee (AK) or below-knee (BK) femoropopliteal revascularization. 5,6 Nonautologous conduit offers a variety of advantages, including shorter operative time, decreased morbidity, and fewer incisions.…”
mentioning
confidence: 99%
“…Adequate full-length venous conduit remains the best bypass option, especially for long multilevel occlusions with published primary patency rates of 84% above knee reverse vein and 82% for infrapopliteal in situ bypass at 1 year. 18,19 In the failed endovascular procedures there may be a question of whether it is worth…”
Section: Discussionmentioning
confidence: 99%